Shifting repertoires: understanding cultural plurality in policing. Issue 2 (2nd April 2016) - Hendriks, Frank; van Hulst, Merlijn
Abstract : The police is one of the most prominent organizations in the frontline of public administration. In order to deal with high external expectations, the organization has been said to develop and nurture multiple police cultures. Applying Grid Group Cultural Theory, or GGCT, we address the following questions: what sets of values, beliefs and practices has the police organization developed to deal with high expectations stemming from their publics? How do cultural tensions play out in real-life practices of policing "under pressure"? We find that cultural patterns described in the general literature on policing can be plotted on the GGCT map. Zooming in on the case of policing in the Netherlands, cultural plurality appears to be not only prominent in the police organization as such, but can also be found in the form of continuous cultural "tap-dancing" – swift, flexible and improvisational shifting – at various levels of active policing.